A Sister Mary Joseph’s nodule in fallopian tube cancer: exploring the metastatic pathway through gene expression profiling—a case report - Takuto Uyama; Yusuke Matoba; Hikaru Nakahara; Akira Ishikawa; Hiroaki Niitsu; Kosuke Nakamoto; Iemasa Koh; Shinji Mii; Takao Hinoi; Kouji Banno (Journal of Medical Case Reports)
Abstract Background A Sister Mary Joseph’s nodule is an umbilical metastasis from an intra-abdominal or pelvic malignancy, associated with a poor prognosis. Three possible metastatic pathways for Sister Mary Joseph’s nodule have been postulated: hematogenous spread, lymphatic dissemination, and direct invasion. However, detailed analyses of these metastatic pathways, particularly those involving gene expression profiling, are lacking in literature. We investigated the metastatic patterns of Sister Mary Joseph’s nodule by performing RNA microarray analysis of the primary tumor and each metastatic site in a case of fallopian tube cancer presenting with Sister Mary Joseph’s nodule and inguinal lymph node metastases. Case presentation A 48-year-old Japanese woman presented with swelling in an inguinal lymph node. Positron emission tomography-computed tomography imaging revealed multiple lymph node metastases, right ovarian tumor, umbilical metastasis, and peritoneal dissemination. The patient underwent a laparoscopic right adnexal resection, left inguinal lymph node biopsy, and umbilical resection. Pathological examination confirmed the diagnosis of primary high-grade serous carcinoma of the right fallopian tube. Metastatic high-grade serous carcinoma was identified in the lymph nodes and umbilical tissue. Tumor tissue samples were collected from the primary lesion, umbilical metastasis, and inguinal lymph node metastasis for RNA microarray analysis. The results showed that genes involved in cell adhesion, migration, and stromal remodeling associated with the metastatic processes were more highly expressed in both inguinal lymph node metastasis and Sister Mary Joseph’s nodule than in the primary lesion. Interestingly, distinct differences in gene expression profiles were observed between umbilical and lymph node metastases, suggesting different metastatic mechanisms. Conclusion Our findings suggest differences in the RNA expression patterns between Sister Mary Joseph’s nodule and lymph node metastases in fallopian tube cancer, indicating the possibility of distinct metastatic mechanisms. Further examination of similar cases and longitudinal studies are necessary to elucidate the metastatic patterns of Sister Mary Joseph’s nodule. This case highlights the potential value of molecular profiling for understanding the complex metastatic processes in gynecological malignancies.